4 Trials of Improved Practices - A Pilot Study Evaluating the Acceptability and Preferences for a Chlorhexidine Cord Care Intervention. (October 2012) - Sazawal, S; Dhingra, P; Dhingra, U; Dutta, A; Ali, SM; Ame, S; Madhesiya, S; Deb, S; Gupta, S; Ahmed, A; Black, RE
Abstract : Background: Chlorhexidine, a broad-spectrum topical antiseptic with strong residual activity, has a potential to reduce infections during the neonatal period. However, the challenge remains what would be the best mode to deliver the intervention. As a part of formative research, we evaluated three possible modes of chlorhexidine delivery i.e. 100ml bottle with cotton swab, 10ml single use dropper bottle and 3g single application squeeze tube containing gel, as an umbilical cord care intervention using Trials for Improved Practices (TIPS) methodology in preparation for a large double-blind randomized controlled trial evaluating the impact of chlorhexidine. in Pemba, Tanzania. Methods: 204 mother-newborn pairs were enrolled from hospital and community setting. Three different modes of application of intervention were tested (3 days for each preparation) in a cross over design. Mothers (on day 10), MCH, TBA and hospital staff was interviewed about their experience and feedback of their preference among the three delivery modes. Convenient and preference scores were calculated based on their feedback. Results: 97% mothers applied intervention for all 9 days. 10ml dropper bottle (49.7%) was rated as most convenient by the mothers, gel tube (32.2%) and 100ml bottle (19.8%). Mothers opted 10ml dropper bottle (44.6%) as their first choice over the 100ml bottle (21.5%) or gel tube (33.9%). MCH/hospital staff's choice was to use gel tube (84%) or 10ml dropper bottle (82%). Conclusions: Overall acceptability was high, in terms of convenience and preference 10ml dropper bottle was a winner. Based on their choice the 10ml dropper bottle was selected for RCT.